Protecting Democracy and the Rule of Law in the European Union: The Hungarian Challenge - Bojan Bugaric (London School of Economics and Political Science (LSE), European Institute, 2014)
After the fall of the Berlin Wall and the collapse of communist regimes, many Central and East European countries successfully managed a 'return to Europe'. For many observers, the 'return to Europe' signaled the ultimate victory of democracy and rule of law over the legacy of totalitarianism in these countries. In contrast to this optimistic view, history is not over and the rising illiberalism in Hungary as well as in some other CEE countries represents a major challenge to liberal democracy. All those who expected that a decade of 'EU accession' for CEE legal regimes would lead to an irreversible break with the totalitarian past were simply naive. They forgot that institutions of liberal democracy cannot be created overnight. It is not only that developing liberal democracy requires more time; it also depends on continuous support and endorsement by the people. The rise of illiberal authoritarianism in Hungary is reminiscent of the dramatic events in Europe's most horrible century. Even if the existence of the EU makes the danger of rising illiberalism less dramatic, there are still reasons to be worried about the authoritarian illiberal attacks on liberal democracy. As the Hungarian case shows, the EU has quite limited powers to effectively prevent the slide to authoritarianism. The irony is that conditionality, so powerful before the CEE countries joined the EU, loses much of its teeth once countries become member states of the EU. Yet, the discussion of the EU instruments to contain such slides into illiberalism has also shown that they are not totally unimportant and that they can be further improved. As I tried to argue, safeguarding democracy and the rule of law in the EU requires serious improvements in the legal toolkit currently available to deal with the slide to authoritarianism in Hungary. Ultimately, EU political actors must respect the limits of the EU political constitution and not attempt to go too far in their otherwise noble aim of protecting democracy in the EU.
Keywords: 330; rule of law; EU; Hungary; Article 7 TEU; Victor Orban; democracy backsliding; illiberalism; Copenhagen Commission